2016
DOI: 10.1111/bre.12217
|View full text |Cite
|
Sign up to set email alerts
|

Oligocene‐Miocene Great Lakes in the India‐Asia Collision Zone

Abstract: The Himalayan-Tibetan Plateau is Earth's highest topographic feature, and formed largely during Cenozoic time as India collided with and subducted beneath southern Asia. The >1300 km long, late Oligocene-early Miocene Kailas basin formed within the collisional suture zone more than 35 Ma after the onset of collision, and provides a detailed picture of surface environments, processes and possible geodynamic mechanisms operating within the suture zone during the ongoing convergence of India and Asia. We present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 104 publications
(163 reference statements)
2
47
0
Order By: Relevance
“…Paleoaltimetry potentiality of branched GDGTs from southern Tibet. DeCelles et al (2016) demonstrated the potential existence of a brief period of lowaltitude topography in the Kailas Basin Suture Zone on the southern TP during the Oligocene-Miocene (26-21 Ma). Using dD wax and MBT/CBT-MAT indices, which themselves have been employed to produce equivalent paleoaltitude estimates, Hren et al (2010) suggested that the northern Sierra Nevada (California, United States) was a warm (i.e., >6-88C warmer than today), high altitude (>2 km asl), and moderate-relief to lowrelief landscape during the Eocene Climatic Optimum (ECO), and throughout the Early Eocene (52-49 Ma; Hren et al, 2010).…”
Section: Citationmentioning
confidence: 95%
See 2 more Smart Citations
“…Paleoaltimetry potentiality of branched GDGTs from southern Tibet. DeCelles et al (2016) demonstrated the potential existence of a brief period of lowaltitude topography in the Kailas Basin Suture Zone on the southern TP during the Oligocene-Miocene (26-21 Ma). Using dD wax and MBT/CBT-MAT indices, which themselves have been employed to produce equivalent paleoaltitude estimates, Hren et al (2010) suggested that the northern Sierra Nevada (California, United States) was a warm (i.e., >6-88C warmer than today), high altitude (>2 km asl), and moderate-relief to lowrelief landscape during the Eocene Climatic Optimum (ECO), and throughout the Early Eocene (52-49 Ma; Hren et al, 2010).…”
Section: Citationmentioning
confidence: 95%
“…Geochemistry, Geophysics, Geosystems PUBLICATIONS sediments dating from the Early Eocene (Anderson et al, 2015;DeCelles et al, 2016;Hren et al, 2010; Table 2). Using dD wax and MBT/CBT-MAT indices, which themselves have been employed to produce equivalent paleoaltitude estimates, Hren et al (2010) suggested that the northern Sierra Nevada (California, United States) was a warm (i.e., >6-88C warmer than today), high altitude (>2 km asl), and moderate-relief to lowrelief landscape during the Eocene Climatic Optimum (ECO), and throughout the Early Eocene (52-49 Ma; Hren et al, 2010).…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high‐quality quantitative data remain scarce, due to the lack of terrestrial paleotemperature reconstruction tools and well‐dated continuous stratigraphic sequences. Microbial‐branched glycerol dialkyl glycerol tetraether (brGDGT) paleotemperature proxies, in the form of the MBT (MBT′)/CBT ratios, have been developed (Weijers et al, ) over the past decade and have been widely used to reconstruct terrestrial paleotemperatures (e.g., Donders et al, ; Weijers et al, ) and paleoaltitudes (Anderson et al, ; DeCelles et al, ; Deng & Jia, ; Hren et al, ; Zhuang et al, ). However, these proxies are affected greatly by alkalinity and aridity (Bai et al, ; Dirghangi et al, ; H. Wang et al, ; H. Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Along the southern flank of the Gangdese Mountains (Fig. 1), an Oligocene-Miocene, conglomerate-rich, continental unit, referred to as the Kailas (Gangrinboche) Formation, is exposed in buttress unconformity atop Gangdese arc rocks (Gansser, 1964;Aitchison et al, 2002;DeCelles et al, 2011DeCelles et al, , 2016Leary et al, 2016b). Nonmarine strata of similar composition and structural position are continuous, with some variations in sedimentary facies, for over 1300 km along the Yarlung suture zone (Leary et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%